Pelatihan Pembuatan Media Pembelajaran Berbahan Ecobricks untuk Guru Sekolah Dasar - Acesta, Arrofa; Solihat, Dadang; Kautsar, Tifani (Program Studi Ilmu Hukum Fakultas Hukum Universitas Kuningan, 2021)
This PKM activity aims to improve the knowledge and skills of elementary school teachers in utilizing ecobricks as a learning medium. Ecobricks are materials derived from plastic waste, such as plastic bottles that cannot be decomposed. The activities are in line with the many problems related to waste, namely: (1) The amount of waste in the school environment that has not been utilized, (2) Lack of understanding and knowledge in processing waste to be used as learning media (3). This training is given to teachers to use ecobricks as a learning medium. The training method is carried out through a process of lectures, demonstrations, questions and answers, and direct practice of making learning media. The results obtained are an increase in the knowledge and skills of elementary school teachers in utilizing ecobricks as learning media.